RELAÇÃO PESO/COMPRIMENTO DAS PRINCIPAIS ESPÉCIES DE PEIXES NOS RIACHOS DA SUB-BACIA DO RIO APA, ALTO RIO PARAGUAI - Mota, Thiago Mota; Alves, Douglas; Rondon, Patrícia; Súarez, Yzel (ANAIS DO ENIC, 2018)
-